Al-Alaqatu Al-Ilmiyati Baina Al-Ulamai Al-Jawina Wa Al-Faulati Al-Usminiyyina Fi Al-Qarni Al-Sadisa Asyara Al-Miladi Ila Qarni Al-Tamina Asyara Al-Miladi - Nuha, Ulin (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2022)
Abstract For approximately five centuries, starting from 1571 and actually ending in 1924, the Ottoman Empire controlled the scientific centers in the Hejaz City. During that time, Ulama Jawi enjoyed the golden age of science. Thoriq Aziz, in his book entitled